Characterization of hotspot exonuclease domain mutations in the DNA polymerase ϵ gene in endometrial cancer - Tian, Wenjuan; Ji, Zhaodong; Wang, Jingshu; Meng, Jiao; Bi, Rui; Ren, Yulan; Shan, Boer; Yang, Gong; Wang, Huaying (Frontiers in Oncology, 2022)
Objective: This study was aimed to identify hotspot exonuclease domain mutations (EDMs) of the DNA polymerase ε gene (POLE) in endometrial cancer (EC) and to investigate the effects of EDMs on tumor cell behavior and catalytic activities of Polε. Methods: POLE sequencing was performed in tumor tissue samples from patients with EC to identify hotspot EDMs. Bioinformatics tools were used to select the potential pathogenic EDMs. The association of EDMs with the clinical outcomes of patients was assessed. EC cells were transfected with wildtype POLE or POLE variants to examine the effects of the EDMs on EC cell behavior , including cell cycle, migration, and invasion. Co-immunoprecipitation was employed to obtain FLAG-tagged wildtype and mutant catalytic subunits of Polε, followed by the assessment of polymerase and exonuclease activities. Results: In addition to previously reported P286R and V411L, R375Q and P452L were identified as novel, and deleterious POLE hotspot EDMs of EC. Patients in EDM group had significantly better clinical outcomes than the rest of the cohort. Compared with wildtype POLE, overexpression of POLE variants promoted cisplatin resistance, G0/G1 cell cycle arrest, and cell migration and invasion in EC cells. Overexpression of POLE variants significantly increased the abundance of 3’-OH and upregulated the expression of DNA mismatch repair genes in HEK293T cells. Compared with wildtype Polε, Pol ε mutants exhibited undermined polymerase and exonuclease abilities in the presence of mismatched nucleotides in HEK293 cells. Conclusion: We identified P286R, V411L, R375Q, and P452L as pathogenic POLE hotspot EDMs in EC. These hotspot EDMs are associated with the malignant behavior of endometrial cancer cells in vitro and favorable prognosis in patients, suggesting that POLE affects a wide range of cellular processes beyond DNA replication and proofreading.